ASSESSMENT OF THE CONDITION OF COMMON AND INTERNAL CAROTID ARTERIES IN STABLE ANGINA PATIENTS WITH GASTRODUODENAL PATHOLOGY - M. N. Prikhodko; K. V. Andreev; Zh. G. Simonova (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To evaluate the characteristics of condition of the common and internal carotid arteries in stable angina patients according to presence of gastrointestinal pathology (GIP).Material and methods. Totally, 68 patients investigated, with stable angina of II-III functional classes. Patients were selected to 3 groups according to the presence and type of GIP: group 1 (n=25) — with chronic gastritis, group 2 (n=25) — with chronic duodenitis, group 3 (control, n=18) — with no GIP. All patients received medication therapy by the standards of care for coronary heart disease patients. Measurement of thickness of intima-media complex (IMC) of common carotid (CCA) and internal carotid (ICA) arteries were done by duplex scanning.Results. It was found that in group 1 patients there is thicker IMC of CCA >0,9 mm comparing to the controls — 44% vs 33,3% (р<0,05). Stenoses of ICA >70% were found only in I and II groups patients — 8% and 12%, respectively (p <0,05), that is an indication for surgical treatment. In the group II there was higher number of patients with plaques in carotid vessel area comparing to group 1 and 3 — 36% vs 20% (р<0,05) and 36% vs 16,7% (р<0,05), respectively. Also, in the group 2 comparing to controls the comparison of lipid profiles showed more prominent increase of triglycerides — 2,2±0,4 vs 1,4±0,2 mM/L (р<0,05). Anamnesis of previous myocardial infarction was more prevalent in group 1 comparing to the 2 and 3 — 60% vs 48% (р<0,05) and 60% vs 50% (р<0,05), respectively.Conclusion. The stable angina patients comorbid by GIP do have more serious atherosclerosis lesion as IMC thickness of CCA and more significant stenosis in ICA, less benign course of cardiovascular disease, that presents as more common development of post infarction cardiosclerosis and hence worse prognosis.